Performance evaluation of Czech innovative companies: data envelopment analysis approach - Žižka, Miroslav; Hovorková Valentová, Vladimíra; Turčok, Lukáš (International Journal of Strategic Property Management, 2016)
The article deals with the verification of a performance evaluation model of innovative companies in the Czech Republic and the evaluation of the impact of a branch on their performance in terms of effectiveness and efficiency. From a methodological point of view, the article is based on the use of Data envelopment analysis (DEA) to evaluate the performance of the selected companies. To evaluate their performance, a two-stage DEA method, BCC model orientated at inputs is used. In the first stage, the effectiveness of resources spent on protecting industrial property rights is evaluated. In the second stage, it is assessed how the companies managed to evaluate registered property rights in terms of added value. The research results show that among branches, there are significant differences in both the overall level of performance, and in its pillars – effectiveness and efficiency. In the conclusion, other potential factors that could affect the company’s performance in terms of effectiveness and efficiency are discussed.First Publish Online: 14 Dec 2016